Republic of Azerbaijan : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report on the Ex Post Assessment of Longer-Term Program Engagement for the Republic of Azerbaijan highlights macroeconomic performance and fiscal policy. On the structural front, significant progress was achieved in fiscal management, the privatization of small- and medium-size enterprises, and trade and price liberalization. Executive Directors underscored that Azerbaijan faces the challenge of achieving sustainable growth of non-oil output, diversifying the economy, and reducing poverty while maintaining macroeconomic stability at a time when oil revenue is projected to increase substantially.